Prognostic value of acetylcholine challenge test: a prospective study. Issue 2 (May 1984) - Pham, Q T; Mur, J M; Chau, N; Gabiano, M; Henquel, J C; Teculescu, D
Abstract : Eleven hundred and nine iron mine workers aged 35 to 55 with normal chest radiographs were submitted to a pulmonary examination consisting of a questionnaire, a clinical examination, and pulmonary function testing including an acetylcholine challenge test. A positive response (decrease of FEV1 of more than 10%) was observed in 210 subjects (Ace+). The remaining 899 had a negative response (Ace-). Bronchitis, asthma, dyspnoea, and obstructive syndrome were more frequent in the Ace+ group. Five years later, 820 subjects were reexamined: occasional cough and sputum and chronic bronchitis appeared more frequently among subjects without symptoms at the first examination but with a positive acetylcholine challenge test. The obstructive syndrome was more often observed and regressed more rarely in the Ace+ group. The results confirm the use of a test of bronchial hyperreactivity as a means of identifying subjects at risk from chronic obstructive lung disease.